Covid-19 Mortality and Contemporaneous Air Pollution - Wes Austin; Stefano Carattini; John Gomez Mahecha; Michael Pesko (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We examine the relationship between contemporaneous fine particulate matter exposure and COVID-19 morbidity and mortality using an instrumental variable approach based on wind direction. Harnessing daily changes in county-level wind direction, we show that arguably exogenous fluctuations in local air quality impact the rate of confirmed cases and deaths from COVID-19. In our preferred high dimensional fixed effects specification with state-level policy and social distancing controls, we find that a one μg/m3 increase in PM 2.5 increases the number of confirmed cases by roughly 2% from the mean case rate in a county. These effects tend to increase in magnitude over longer time horizons, being twice as large over a 3-day period. Meanwhile, a one μg/m3 increase in PM 2.5 increases the same-day death rate by 3% from the mean. Our estimates are robust to a host of sensitivity tests. These results suggest that air pollution plays an important role in mediating the severity of respiratory syndromes such as COVID-19, for which progressive respiratory failure is the primary cause of death, and that policy levers to improve air quality may lead to improvements in COVID-19 outcomes.
Keywords: D62; I10; Q53; 330; pollution; air quality; PM 2.5; COVID-19; health; mortality